Perkembangan Eksperimen Fisika Ditinjau dari Filsafat Sains - Festiana, Ike (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2018)
Scientific knowledge as well as experiment keeps on growing every day. Experiments flourished in the seventeenth century. Previously, information about world development was obtained by connecting the roles of prominent epistemology. Experimentation is defined as a planned program for restoring hypotheses by providing empirical evidence to people. Science is a process of seeking the truth. Activities in finding the truth involves a series of scientific method including experiment. The development of physics history is divided into five periods. Period one is indicated by the absence of systematic and independent experiment. In period two, experimental methods had been accountable, and well accepted as a scientific issue. In period three, (investigations developed more rapidly when classical physics development began to be foundation of current famous quantum physics). Period four which is called The Old Quantum Mechanics is indicated by the invention of microscopic phenomena. Period five is well known by the emergence of new quantum mechanics theory.